Relaxation processes in barium strontium titanate glass‐ceramics by thermally simulated depolarization current. Issue 3 (16th October 2018) - Song, Xiaozhen; Zhang, Tianyuan; Zhao, Zhangyuan; Hu, Kangjia; Baturin, Ivan; Shur, Vladimir; Zhang, Yong
Abstract: Thermally stimulated depolarization current (TSDC) experiments were carried out to investigate the effect of polarization temperature on different relaxation processes in barium strontium titanate glass‐ceramics. It was found that all the TSDC curves are composed of four relaxation peaks. From the characteristics of peak temperature and peak current intensity with various polarization temperatures, the origin of these four peaks are identified as from defect dipole orientation, charge carrier detrapping, in‐crystal oxygen vacancy migration, and trans‐interface oxygen vacancy migration respectively. In addition, both the dipole concentration and trap density for the glass‐ceramic samples were estimated.